The development of a recovery coaching training curriculum to facilitate linkage to and increase retention on medications for opioid use disorder - Moffitt, Trevor; Fallin-Bennett, Amanda; Fanucchi, Laura; Walsh, Sharon L.; Cook, Christopher; Oller, Devin; Ross, Anna; Gallivan, Molly; Lauckner, John; Byard, Jeremy; Wheeler-Crum, Phoebe; Lofwall, Michelle R. (Frontiers in Public Health, 2024)
The authors wish to acknowledge the recovery coaches and supervisors at Voices Hope for their work in operating the linkage and retention programs and co-facilitating portions of the training program. The authors also wish to acknowledge the study's implementation facilitators for their work in coordinating the recovery coaches' agency placements. The authors also wish to acknowledge the participation of the HEALing Communities Study communities, community coalitions, Community Advisory Boards, agency partners, and state government officials who partnered with us on this study.